Cold iron task - Butcher, James J. (Butcher, James J. Unorthodox chronicles, 2025)
"Grimsby, a junior Auditor in the magical Department of Unorthodox Affairs, finds himself on the other side of the law in this spellbinding urban fantasy. Grimshaw Griswald Grimsby may have one case under his belt, but he's still a novice Auditor in Boston's Department of Unorthodox Affairs. And he's already made mistakes. Desperate to repair his fraying friendships, he doesn't ask too many questions when a mysterious patron offers him the chance to join a heist of an otherworldly vault--and in the process find answers that could make things right. Complications arise when Grimsby learns that his partner, Leslie Mayflower, is keeping secrets about his past. Between facing new demons, old horrors, and monsters--both Usual and Unorthodox--Grimsby soon realizes that nothing is how it appears, and not asking enough questions just might be his downfall."--